Constraints of Weight Loss as a Marker of Bariatric Surgery Success: An Exploratory Study - Gil, Saulo; Goessler, Karla; Dantas, Wagner S.; Murai, Igor Hisashi; Merege-Filho, Carlos Alberto Abujabra; Pereira, Rosa Maria R.; de Cleva, Roberto; Santo, Marco Aurélio; Kirwan, John P.; Roschel, Hamilton; Gualano, Bruno (Frontiers in Physiology, 2021)
Purpose: The aim of this exploratory study was to investigate whether the degree of weight loss reflects improvements in cardiometabolic health among patients who underwent Roux-en-Y gastric bypass. Methods: In this ancillary analysis from a clinical trial, patients were clustered into tertiles according to the magnitude of the percentage weight loss (1st tertile:“higher weight loss”: -37.1±5.8%; 2nd tertile:“moderate weight loss”: -29.7±1.4%; 3rd tertile:“lower weight loss”: -24.2±2.3%). Delta changes (9-months after surgery-baseline) in clustered cardiometabolic risk (i.e., blood pressure index, fasting glucose, high-density lipoprotein [HDL] and triglycerides [TG]), glycated hemoglobin (HbA1c), homeostasis model assessment (HOMA-IR) and C-reactive protein (CRP) were calculated. Results: 42 patients who had complete bodyweight data (age=40±8yr; BMI=47.8±7.1 kg/m2) were included. Surgery led to substantial weight loss (-37.9±11.3 kg, P<0,001), and clinically significant improvements in blood pressure index (-17.7±8.2 mmHg, P<0.001), fasting glucose (-36.6±52.5 mg/dL, P<0.001), HDL (9.4±7.1 mg/dL, P<0.001), TG (-35.8±44.1 mg/dL P<0,001), HbA1c (-1.2±1.6%, P<0.001), HOMA-IR (-4.7±3.9 mg/dL, P<0.001) and CRP (-8.5±6.7 µg/mL P<0.001). Comparisons across tertiles revealed no differences for cardiometabolic risk score, fasting glucose, HbAc1, HOMA-IR, blood pressure index, CRP, HDL, and TG (P>0.05 for all). Individual variable analysis confirmed cardiometabolic improvements across the spectrum on weight-loss. There were no associations between weight loss and any dependent variable. Conclusion: Weight loss following bariatric surgery does not correlate with improvements in cardiovascular risk factors. These findings suggest that weight loss alone may be insufficient to assess the cardiometabolic success of bariatric surgery, and the search for alternate proxies that better predict surgery success are needed.